Advances in human factors and systems interaction : proceedings of the AHFE 2019 International Conference on Human Factors and Systems Interaction, July 24-28, 2019, Washington D.C., USA /: proceedings of the AHFE 2019 International Conference on Human Factors and Systems Interaction, July 24-28, 2019, Washington D.C., USA. ([2020]) - Unknown
No abstract available